Potential Plants With Antidiabetic Activity In Glut-4 Translocation: A Narrative Review - Rabiatul Adawiyah; Ayu Shabrina; Sapto Yuliani; Nurkhasanah Nurkhasanah (Universitas Wahid Hasyim Semarang, 2023)
Diabetes Mellitus (DM) is a chronic disease caused by decreased activity of the pancreas in producing insulin. Insulin resistance is characterized by decreased synthesis and translocation of GLUT-4 to cell membranes, GLUT-4 can be found in several tissues, but mainly in muscle and adipose tissue. The purpose of this study was to identify plants that have antidiabetic activity in Glut-4 translocation and further can be used as reference material in research. This research method is Article Review, by searching for articles published in 2013-2023 in the Pubmed, Google Scholar, Proquest, Springer Link, and Science Direct databases. The sample in this study was in the form of research articles that met the inclusion criteria and obtained a total of 15 articles. The results of this study showed that there was significant antidiabetic activity from the administration of Ethanol Extract on 125 mg/kg BW of Salam Leaf, 200 mg/kg BW of Areca Nut, 200 mg/kg of Papaya Seed, 96 mg/kg of Black Cumin, Combination of Sambiloto Leaf and Gotu kola leaves 300 mg/kg BW, 400 mg/kg BW of Adem Ati Bark, 100 mg/kg BW of Artemisia Leaf, 250 mg/kg BW of Coffee Beans, 200 mg/kg BW of Tapak Dara Leaves, 300 mg/kg BW of Puguntano Leaves, 50 mg/kg BW of Ginger, and 200 mg/kg BW of Cinnamon. These plant extracts have antidiabetic activity as GLUT4 translocates to the plasma membrane of muscle cells. The bioactive compounds contained in them which act as antidiabetic activity are flavonoids, saponins and tannins.